1998
DOI: 10.1074/jbc.273.22.13444
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Regulation of Inducible Nitric-oxide Synthase in Macrophages by Atrial Natriuretic Peptide

Abstract: Atrial natriuretic peptide (ANP), a cardiovascular hormone, has been shown to inhibit synthesis of nitric oxide in lipopolysaccharide (LPS)-activated mouse bone marrow-derived macrophages via activation of its guanylate cyclase-coupled receptor. The goal of the present study was to elucidate the potential sites of inducible nitric-oxide synthase (iNOS) regulation affected by ANP and revealed the following. 1) ANP and dibutyryl-cGMP did not inhibit catalytic iNOS activity measured by the conversion rate of L-[ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
79
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 50 publications
5
79
2
Order By: Relevance
“…In contrast to nNOS and eNOS, the activity of iNOS is independent of intracellular Ca 2ϩ , and its mRNA expression is enhanced by lipopolysaccharide or cytokines (19,37,38). Interestingly, several investigators reported that ANP affected NO production probably by modulating expression of iNOS mRNA in human proximal tubule cells (5,24) or mouse macrophages (13,14). However, the present study showed that hANP activated the channel even when the NOS inhibitor or ODQ was present in the bath.…”
Section: Discussioncontrasting
confidence: 50%
“…In contrast to nNOS and eNOS, the activity of iNOS is independent of intracellular Ca 2ϩ , and its mRNA expression is enhanced by lipopolysaccharide or cytokines (19,37,38). Interestingly, several investigators reported that ANP affected NO production probably by modulating expression of iNOS mRNA in human proximal tubule cells (5,24) or mouse macrophages (13,14). However, the present study showed that hANP activated the channel even when the NOS inhibitor or ODQ was present in the bath.…”
Section: Discussioncontrasting
confidence: 50%
“…Recent evidence has suggested that ANP also influences the functions of immune cells: ANP stimulates migration of human neutrophils (7), inhibits proliferation of rat thymocytes (8), enhances human NK cell cytotoxicity (9), and inhibits NO and TNF-␣ production of murine macrophages (10,11). The last effect may be related to the previous observation that ANP could attenuate ischemia-reperfusion injury of the liver via GC-A (12).…”
mentioning
confidence: 71%
“…Taken together, it is strongly suggested that the observation described in this study has certain physiological relevance. Considering that GC-A is expressed on macrophages (2) and DCs as we report but not on monocytes, ANP is likely to exert its immunoregulatory actions in tissue microenvironments, where the paracrine or autocrine mechanism of ANP may take place (2,10). Further studies are required to define the roles of ANP and GC-A in immune regulation in vivo and to better understand the cross-talk between the reno-cardiovascular system and the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is well established in neutrophils and has been suggested to be the case for macrophages (54,55). cGMP in macrophages has been shown to modulate inflammatory processes, such as inducible NO synthase induction (56,57) and TNF-␣ release (58)(59)(60)(61). Also, it is known that intracellular calcium transients are important modulators of macrophage (62)(63)(64) function.…”
Section: Discussionmentioning
confidence: 99%